Pengaruh Campaign #LanjutTerus Rexona Melalui Media Sosial Instagram Terhadap Brand Awareness - Utomo, Hajeng Herika; Prahesti, Riska Tyas (Media Bahasa, Sastra, dan Budaya Wahana, 2025)
#LanjutTerus is a campaign created by Rexona that aims to support Indonesian people to face their doubts and try their first step. The Instagram social media platform was chosen as the media used to disseminate the #LanjutTerus campaign. Brand awareness is the ability of consumers to remember a product or brand in a certain category. The purpose of this research is to find out how much influence the #LanjutTerus Rexona campaign through Instagram has on brand awareness. This research uses a quantitative approach and is analyzed to produce accurate data. The quantitative method is used to see the effect of the #LanjutTerus Rexona campaign through Instagram social media (X) on brand awareness (Y). The type of research used in this research is explanatory and positivistic, and the method used is conducting a survey. Data collection is done by non-probability sampling with the criteria of following the @rexona_id Instagram account and knowing the #LanjutTerus campaign. The number of samples in this study was 86, calculated using the Taro Yamane formula. The data were collected through a Google form and processed with SPSS 26. The result of this research shows that the #LanjutTerus Rexona campaign through Instagram has a very low effect on brand awareness. This research identifies that the campaign through Instagram social media makes a positive contribution. It can be seen from the high score on the statement, “Through Instagram, the #LanjutTerus campaign can be conveyed well, such as message and visual content”.